Poultry farmers and breeders, animal scientists, veterinarians. - GBADAMOSI, A.J.; EGBUNIKE, G. N. (Nigerian Journal of Animal Science, 2022)
The effects of frequent ejaculation and breed on the semen characteristics of cocks were studied using eightem cocks made up of twelve nine-month old exotic cocks (six Harco and six Anak strains) and six mature local cocks of unknown ages. The cocks were ejaculated once, twice or thrice per day for a seven-day period?. in a change over design. In all the breeds, the colour of the ejaculates was creamy, milky white or watery while significant (P < 0.05) breed differences wele observed in ejaculate volume, sperm concentration, sperm output and sperm motility with the heavier breeds being superior to the lighter indigenous cocks. Percentage dead sperm was not influenced by breed. Frequent ejaculation resulted in a significant (P < 0.05) decrease in semen volume, sperm motility, sperm concentration and sperm output and a significant (P < 0.05) increase in % abnormal sperm. The study showed that frequent ejaculation could have adverse effect on the quality of ejaculates and thus fertilizing capacity, with the exotic cocks however having a higher quality semen over the local cocks.